Gamified EFL learning: Utilizing 4 Pics 1 Word Application in Vocabulary Class - Devika Adelita; Rahmah Fithriani (English Department - University of Sultan Ageng Tirtayasa, 2023)
Mobile devices are widely utilized today in language classrooms across the globe, and experts have studied this phenomenon. This study examines the use of mobile devices and the 4 Pics 1 Word application (app) to support English language learning. This study seeks to investigate students’ perceptions of 4 Pics 1 Word app utilized in vocabulary class, specifically in terms of its benefits. Using a qualitative case study design, 40 EFL students attending a junior high school in Medan participated in this study. The data were collected through questionnaires containing ten statements in which the answer options are strongly agreed, agreed, neutral, disagreed, and strongly disagree; and semi-structured interview, which was done with five students who voluntarily participated. The findings indicate that students viewed the use of 4 Pics 1 Word in vocabulary class positively. It is believed that the application is efficient and well-designed, with an exciting and enjoyable learning environment. Enhanced learning motivation and interest, increased vocabulary mastery, and a more active and enjoyable learning process are among the benefits mentioned by the students.